Interior as Ecosystem - Atmodiwirjo, Paramita; Yatmo, Yandi Andri (UI Scholars Hub, 2025)
The idea of interior as an ecosystem views the emergence of interior as a dynamic and relational environment. Rather than viewing the interior as a static or enclosed environment, the ecological perspective considers the interior as an ecosystem, constructed by the systems of relations that involve a multiplicity of actors and entities. This issue of Interiority presents the emergence of various interior occupation and adaptation models that have emerged as an integral part of the ecosystem. The collection of articles in this issue presents a range of cases, ranging from traditional, modern, to contemporary lifestyles and contexts. The works demonstrate the ecosystem involving various actors, both human and non-human, across cultures and time periods. They represent the acts of responding and manoeuvring within the ecological entanglement. They illustrate how interior is not merely a backdrop of living but dynamic agents that keep evolving and transforming within the dynamic ecologies.